2016
DOI: 10.1111/1467-954x.12377
|View full text |Cite
|
Sign up to set email alerts
|

With a little help from my friends: relational work in leisure-related enterprising

Abstract: The present article analyses the indistinct boundaries between formal and informal economic exchanges, with a focus on friendship and work relations. To illustrate these intersections, we present a study of Swedish lifestyle entrepreneurs who run small-scale horse-related enterprises. The specific characteristics of this form of business -in which the horse farm owners/operators, customers, employees and voluntary workers share a leisure interest in horses and participate in the everyday work on the farm -prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…They are invested in, and dependent on, their relationships with local people, businesses and associations. As other recent studies have concluded, without the help of alters in the owner-managers' inner circle and other informal local relationships, many tourism micro-firms could hardly operate feasibly (Cederholm & Åkerström, 2016;Kc et al, 2019a;Rebelo, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…They are invested in, and dependent on, their relationships with local people, businesses and associations. As other recent studies have concluded, without the help of alters in the owner-managers' inner circle and other informal local relationships, many tourism micro-firms could hardly operate feasibly (Cederholm & Åkerström, 2016;Kc et al, 2019a;Rebelo, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, many craft distillers recalled how they drew on family and friends as a source of informal ad hoc labour where, as Austin explained, 'you find mum, dad, an uncle, or whoever really, are willing to lend a hand partly in the hope of getting some nice free gin to drink at the end of the day'. Such is akin to the 'helping hands' identified by Cederholm and Åkerström (2016), where the intersection of gift and market economies becomes visible through the assistance and mutual support offered by friends and family. A significant number of the distilleries studied developed in this way, with family and friends being the tasters whose positive response would then provide the confidence to take the first steps in commercial enterprise.…”
Section: 'It Was Me a Few Close Friends And A Table Full Of Booze': mentioning
confidence: 99%
“…Entrepreneurial labour has been described as an expression of selfhood and individual identity (Bröckling, 2015) which is supported by a widely accepted ‘cultural myth’ that the domains of work and family are distinct and separate (Fitzgerald & Muske, 2002). However, as part of debates which have sought to challenge this dichotomous separation of work and non-work spheres (Land & Taylor, 2010; Smith Maguire, 2017), there has been a move to explore the ‘increasingly porous’ boundaries between the personal and professional lives of entrepreneurs (Wee & Brooks, 2012, p. 574) and to better understand the ways in which some occupational cultures ‘strongly value the blurring of boundaries between work and leisure, and between friends and formal work relations’ (Cederholm & Åkerström, 2016, p. 751). Additionally, the resurgence of academic interest in the concept and practice of craftwork (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, boundaries may cause particular confusion when working at home with customers who come there, as is the case in this study. Hosting businesses are generally good examples of this acute emotional dilemma regarding what is private and what is public (Brandth and Haugen 2012;Cederholm 2015;Cederholm and Hultman 2010;Cederholm & Åkerström 2016;Di Domenico and Lynch 2007;Lashley and Morrison 2003). Such work makes several boundaries more apparent.…”
Section: Work-life Boundaries In 'Old' and 'New' Workmentioning
confidence: 99%
“…The entrepreneurs had lifestyle-driven intentions behind their decisions to move to rural areas (also, Ateljevic and Doorne 2000;Cederholm and Hultman 2010;Cederholm and Åkerström 2016;Hall 2009). This background makes them different from those actors who commercialize their inherited rural homes by providing rural idyll and traditions.…”
Section: The Dream Of Self-established Boundariesmentioning
confidence: 99%